Integration Model of Green Property and Digital Marketing in Business Development Strategies for Land Plotting in Bali Province - Theodorus Hadrianus Gabriel Asy; Yulianto Umar Rofi’i (International Journal of Management Science and Information Technology, 2026)
This research seeks to analyze the synergy between Green Property principles and Digital Marketing strategies in the development of land plotting in Bali. As climate change poses significant challenges and public awareness of environmental issues grows, property developers must embrace environmentally responsible practices. Employing a quantitative methodology, data was gathered from property stakeholders throughout various regions in Bali via surveys. The findings reveal that adopting eco-friendly technologies, such as renewable energy and sustainable building materials, significantly enhances the appeal of land plotting products to consumers. Furthermore, effective Digital Marketing strategies, including the use of social media and captivating visual content, are vital for establishing brand identity and improving product visibility in a competitive landscape. Although developers face obstacles related to digital skills and marketing comprehension, this study uncovers opportunities for a cohesive integration of both approaches. Recommendations emphasize the necessity for developers to invest in digital skills training and foster collaborations to create more impactful marketing strategies. By embracing Green Property principles alongside Digital Marketing, developers can solidify their market position while actively contributing to environmental sustainability in Bali.